The Geographic Analysis of Cotton Production in the Mississippi Delta and Black Belt of the American South - Grubb, Tracey; Mertig, Darin (My University, 2009)
The Delta Blues region in the southern United States is a unique region both in the physical and cultural landscape and is different from its surrounding regions. This project will analyze changes in agriculture throughout the Delta and the Black Belt. This data will be analyzed using GIS spatial models to create spatial models of the changes that have occurred throughout these decades.
Color poster with text and maps (Spring 2009)
Keywords: Delta (Miss. : Region)--Commerce--History; Black Belt (Ala. and Miss.)--Commerce--History; Cotton growing--Delta (Miss. : Region); Cotton growing--Black Belt (Ala. and Miss.); Posters